Languages in the Lutheran reformation : textual networks and the spread of ideas - Kauko, Mikko, 1983-; Norro, Miika; Nummila, Kirsi-Maria; Toropainen, Tanja; Fonsén, Tuomo, 1976- (Crossing boundaries: Turku medieval and early modern studies., 2019)
This multi- and cross-lingual collection of articles charts the influence of the Lutheran Reformation on various Northern European languages and texts written in them. While there are many studies on the internal developments of individual languages during the Reformation, very little has been written about influences between these languages. Mobility, networks of texts, knowledge and authors, and the exchange of ideas and the spread of reformatory thought belong to the topics of the present volume. The articles look into language use, language culture, and translation activities during the Reformation, but also leading to the Reformation as well as following from it later on in the Early Modern period. The contributors are experts in the study of their respective languages, including Czech, Danish, Dutch, English, Estonian, Finnish, High German, Icelandic, Latvian, Lithuanian, Low German, Polish and Swedish. The primary texts explored in the articles include Bible translations, hymns and other printed or handwritten materials.